Ralph Penny, Variation and change in Spanish. Cambridge University Press, Cambridge, 2000; xiv + 284 pp. - Martín Butragueño, Pedro (Nueva Revista de Filología Hispánica (NRFH), 2002)
Se reseñó el libro: Variation and change in Spanish.